The Process of Erection of the Bishopric of Aguascalientes, Mexico (1869-1899) - Rodríguez López, María Guadalupe (2023)
This article studies the erection process of the bishopric of Aguascalientes in the last decades of the 19th century. The linking of various religious, economic, political, and social factors, in conjunction with the interests of both the lay Catholic people and ecclesiastical elites, allowed the establishment of the episcopal see of Aguascalientes within the context of the territorial reorganization and social recomposition of the Church in Mexico, promoted from the Holy See by Pope Leo XIII. The particularity of this erection lies in the small territorial extension with which it was formed and the strong opposition presented by the Archbishopric of Guadalajara, which even managed to stop the project at a certain point.